The use and function of Scripture in 1 Maccabees - Choi, Dongbin (2017)
The present study investigates the characteristics and function of Scripture in 1 Maccabees. It argues that the author of 1 Maccabees locates the history of the Hasmonean revolt within the continuing history of Israel in accordance with the Deuteronomic covenantal concept, portraying the Hasmoneans as salvific figures comparable to Jewish ancestral heroes in Scripture, thereby legitimising the pre-monarchical Hasmonean institution in the late period of the reign of John Hyrcanus I. After discussing scholarly literature on the use and function of Scripture in 1Maccabees in Chapter 1, Chapter 2 discusses various literary, political and cultural aspects: 1) I identify the iimplications of the loss of the original Hebrew text of 1 Maccabees, defining some limitations for morphological analysis; 2) I demonstrate that most books of the present canon of the Hebrew Bible can be identified as available sources to the author; 3) The date of the composition is identified as the later reign of John Hyrcanus I; 4) I further discuss the extent of Hellenistic influence in 1 Maccabees, concluding that 1 Maccabees demonstrates Jewish tradition to a large extent; 5) Finally, I discuss the Jewish perception of the past in antiquity, arguing that Jews had a special interest in preserving their ancestral past in comprehensive and unitary ways without easily manipulating it. Chapters 3 and 4 provide an analysis of philological and conceptual parallels between Scripture and 1 Maccabees, with the conclusion that the use of Scripture mainly functions to provide the intellectual tool for seeing the Hasmonean rule as a further re-enactment of the scriptural precedents of Israel’s restoration and triumph over their enemy and fulfilment of prophecies. Chapter 5 analyses use of Scripture in the eulogies of the Hasmoneans, reaching the same conclusion as the preceding two chapters. In contrast to the scholarly view that 1 Maccabees is Hasmonean propaganda with a politically intended manipulation of Jewish tradition, the present study suggests it as an attestation to traditional Jewish values without radical departure from them.